2017
DOI: 10.3892/ol.2017.6678
|View full text |Cite
|
Sign up to set email alerts
|

Elacridar, a third-generation ABCB1 inhibitor, overcomes resistance to docetaxel in non-small cell lung cancer

Abstract: Abstract. Docetaxel is a third-generation chemotherapeutic drug that is widely used in the treatment of patients with non-small cell lung cancer (NSCLC). However, the majority of patients with NSCLC eventually acquire resistance to the treatment. In the present study, the mechanism of acquired resistance to docetaxel treatment in lung cancer cells was investigated. The three NSCLC cell lines, H1299 with wild-type epidermal growth factor receptor (EGFR), EGFR-mutant HCC4006 and HCC827, and experimentally establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…We found that elacridar recovered the sensitivity to docetaxel, but not to afatinib in H2170‐ARS and H2170‐ARH cells. These findings were similar to those in our previous report using docetaxel‐resistant NSCLC cells with EGFR‐ mutations . In contrast, the other afatinib‐resistant cell lines, including Calu3‐ARH, H1781‐ARS and H1781‐ARH, which showed EMT or had acquired CSC‐like features, showed maintained sensitivity to docetaxel, because ABCB1 was not upregulated in these acquired resistance cell lines.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…We found that elacridar recovered the sensitivity to docetaxel, but not to afatinib in H2170‐ARS and H2170‐ARH cells. These findings were similar to those in our previous report using docetaxel‐resistant NSCLC cells with EGFR‐ mutations . In contrast, the other afatinib‐resistant cell lines, including Calu3‐ARH, H1781‐ARS and H1781‐ARH, which showed EMT or had acquired CSC‐like features, showed maintained sensitivity to docetaxel, because ABCB1 was not upregulated in these acquired resistance cell lines.…”
Section: Resultssupporting
confidence: 90%
“…These findings were similar to those in our previous report using docetaxel-resistant NSCLC cells with EGFR-mutations. 32 In contrast, the other afatinib-resistant cell lines, including…”
Section: Sensitivity Of the Afatinib-resistant Cells To Chemotherapmentioning
confidence: 99%
“…YHO-13351 is a potent inhibitor of ABCG2, and its combination with irinotecan effectively targets CSC from cervical carcinoma preventing resistance and tumor relapse [88]. Elacridar is a third-generation competitive inhibitor of ABCB1 that reverses multidrug resistance of lung cancer, sensitizing cancer stem cells to docetaxel [89]. In breast cancer, ABCC1 and ABCC3 transporters are implicated in multidrug resistance and are increased after chemotherapy.…”
Section: Strategies To Target Cancer Stem Cellsmentioning
confidence: 99%
“…Thus, the detection of FABP4 is helpful for predicting the prognosis of patients with NSCLC [70]. ABCB1 reportedly plays an important role in overcoming ABCB1mediated docetaxel resistance in lung cancer [71].…”
Section: Discussionmentioning
confidence: 99%